PEMAHAMAN LITERASI KEUANGAN TERHADAP LAPORAN KEUANGAN UMKM DI DESA SUNGAI DUREN - Nurfitri Martaliah; Ilham Wisnu Herlambang; Trias Yudana (Nusantara Hasana Journal, 2025)
This study aims to investigate the extent of understanding among Micro, Small, and Medium Enterprises (UMKM) regarding the role and benefits of financial reports. Although financial reports are vital for business continuity, many UMKM still do not understand and apply them properly. This study employed a descriptive qualitative approach by conducting in-depth interviews with eight UMKM in Sungai Duren Village engaged in the culinary, craft, and service sectors. The research findings indicate that the majority of UMKM only record basic transactions and have not yet prepared formal financial reports. The main causes of this low understanding are a lack of accounting education, limited training, and the perception that financial reports are only relevant for large companies. Relevant mentoring and education are needed so that UMKM can understand and utilize financial reports to develop their businesses.